2022
DOI: 10.1080/21655979.2021.2021065
|View full text |Cite
|
Sign up to set email alerts
|

Ramelteon protects against human pulmonary microvascular endothelial cell injury induced by lipopolysaccharide (LPS) via activating nuclear factor erythroid 2-related factor 2 (Nrf2)/heme oxygenase-1 (HO-1) pathway

Abstract: Acute lung injury (ALI) is classified as a moderate or mild acute respiratory distress syndrome and is a prominent cause of morbidity and mortality among the critically ill population. Ramelteon is a melatonin receptor agonist with anti-inflammatory and antioxidant effects. The current study investigated the role of ramelteon in lipopolysaccharide (LPS)-induced human pulmonary microvascular endothelial cells (HPMECs) and its potential regulatory mechanisms. A CCK-8 assay was used to examine the effect of ramel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Leng et al [ 5 ] found that the abnormal apoptosis of PMVECs was the primary cause of pulmonary vascular dysfunction and pivotal for the onset and development of ALI. Therefore, deeply investigating the mechanism of PMVEC apoptosis in disease progression and seeking for new antiapoptotic drugs or therapeutic methods are highly constructive for potentiating the pulmonary function and relieving the clinical symptoms of patients [ 6 ]. Wu et al [ 7 ] reported that large quantities of regulatory genes (microribonucleic acid (miR)-339-3p, miR-4262, and so on.)…”
Section: Introductionmentioning
confidence: 99%
“…Leng et al [ 5 ] found that the abnormal apoptosis of PMVECs was the primary cause of pulmonary vascular dysfunction and pivotal for the onset and development of ALI. Therefore, deeply investigating the mechanism of PMVEC apoptosis in disease progression and seeking for new antiapoptotic drugs or therapeutic methods are highly constructive for potentiating the pulmonary function and relieving the clinical symptoms of patients [ 6 ]. Wu et al [ 7 ] reported that large quantities of regulatory genes (microribonucleic acid (miR)-339-3p, miR-4262, and so on.)…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the Nrf2/HO-1 pathway not only eliminates ROS but also effectively regulates inflammatory responses [ 35 ]. Those compounds that promote HO-1 expression, such as notopterol, nepetoidin B, and ramelteon, can inhibit inflammation, but their effects can be weakened by HO-1 inhibitors [ 38 , 39 , 40 ]. Therefore, we tested whether EAF exerts antioxidant effects and alleviates inflammation by upregulating the Nrf2/HO-1 pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Ramelteon is a selective MT1/2 receptor agonist and is predominantly used to treat difficulty falling asleep ( 24 ). In recent years, numerous studies have suggested that ramelteon protects against injury on human tissues induced by oxidative stress and LPS ( 17 , 25 , 26 ). The current study specified that ramelteon attenuates renal IRI and H/R-induced apoptosis by mitigating ROS generation, mitochondrial injury, and inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…HK-2 cells were randomly divided into five groups: (I) control; (II) H/R; (III) H/R + ramelteon (10 nM); (IV) H/R + ramelteon (30 nM); and (V) H/R + ramelteon (60 nM). Ramelteon concentrations were determined based on previous studies ( 16 , 17 ). HK-2 cells were prophylactically treated with ramelteon and then exposed to H/R.…”
Section: Methodsmentioning
confidence: 99%